ANALISIS PERBANDINGAN RASIO PROFITABILITAS SEBELUM DAN SELAMA PANDEMI COVID - 19 PADA PERUSAHAAN UMUM DAMRI - Jalal Luddin; Adif Fachrudin; Adelina Citradewi (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This study was conducted to compare profitability ratios using Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Operating Profit Margin (OPM) methods in Perum Darmri before and during the covid-19 pandemic. The data used were secondary data obtained from the official website of Perum Damri using Perum Damri's financial reports for 2018-2021. The analysis technique used was quantitative comparison. The results showed that there was no difference in the profitability ratios of the Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM) methods at the beginning of the pandemic covid-19 and during the pandemic covid-19 only the Operating Profit Margin (OPM) there was a difference at the beginning of the pandemic covid-19 from another method. At the beginning of the pandemic covid-19, Perum Damri experienced an increase in Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) methods but experienced a decrease in the Operating Profit Margin (OPM) method. During the pandemi covid-19 or during the pandemic covid-19, Perum Damri experienced a decrease in each ratio method used, both Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM) and Operating Profit Margin (OPM).